Banglapedia : national encyclopedia of Bangladesh [ Bangla version , Volume 2] - Islam, Sirajul, 1939-; Asiatic Society of Bangladesh (Dhaka : Asiatic Society of Bangladesh, 2003)
On various subjects pertaining to Bangladesh.
Reference
Also issued on CD-ROM, and on the World Wide Web.
Keywords: Bangladesh -- Encyclopedias